2014
DOI: 10.1002/app.40842
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental influences on quasistatic and cyclic material behavior of short glass fiber reinforced polyamide illustrated on microscopic scale

Abstract: In this work, the influences of fiber orientation and weld lines on the morphological structures and the mechanical behavior of polyamide 6.6 (PA6.6-GF35) are investigated. In quasistatic and fatigue tests tensile and 3-point-bending loads are applied. Test temperatures vary between RT and 150 C. Two different specimen types are produced by using injection moulding process to create different fiber orientations as well as weld lines. Fiber orientations are determined using computer tomography. Scanning electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Bernasconi et al [16] showed that increasing specimen orientation angle decreases elastic modulus, ultimate tensile stress and fatigue strength. The same results was found by Zhou and Mallick [15] and Brunbauer et al [17]. Recently, Benaarbia et al [18], reported that ratcheting for fibre reinforced composites oriented at 45° and 90° was much higher than that for 0° composites Moreover, Mallick and Zhou [19] evaluated the effect of the stress ratio on the fatigue behaviour of the PA66-GF33.…”
supporting
confidence: 73%
“…Bernasconi et al [16] showed that increasing specimen orientation angle decreases elastic modulus, ultimate tensile stress and fatigue strength. The same results was found by Zhou and Mallick [15] and Brunbauer et al [17]. Recently, Benaarbia et al [18], reported that ratcheting for fibre reinforced composites oriented at 45° and 90° was much higher than that for 0° composites Moreover, Mallick and Zhou [19] evaluated the effect of the stress ratio on the fatigue behaviour of the PA66-GF33.…”
supporting
confidence: 73%
“…Matrix brittle failure and fiber pull-out were observed in mold flow oriented samples, while brittle fracture surface was observed in samples perpendicular to the mold flow direction of short glass fiber polyamide-6.6 in [15]. As temperature increased, crazes in fibril structure were more pronounced.…”
Section: Introductionmentioning
confidence: 87%
“…Evolution of hysteresis loops in either their size or slope [2,5], hysteretic energy [7,8], strain energy [9,10], and nonlinear viscoelasticity [11,12] are the parameters typically used for modeling of fatigue damage and accumulation. Fiber orientation is another important factor controlling fatigue performance and the degree of anisotropy of SFRPCs [13][14][15]. The orientation distribution of fibers is mainly controlled by a complex flow field in the injection molding process and also dependent on the geometry of fibers and the component, viscoelastic behavior of matrix, and melt and mold temperatures [16].…”
Section: Introductionmentioning
confidence: 99%
“…The work of Horst and Spoormaker [ 28,29 ] on the damage mechanisms of short glass fiber polyamide 6.6 in quasi‐static and fatigue allowed proposing a scenario of damage in fatigue similar to that of Sato, [ 30,31 ] mainly based on the creation of a vacuum at the matrix fiber interface. Since then, this scenario has been widely validated in the literature [ 32,33 ] and has affirmed its independence from many parameters, including the type of loading and the temperature. For both researchers, the difference between each loading would lead to the level of the kinetics of the damage propagation.…”
Section: Introductionmentioning
confidence: 98%